Determination of heavy metals in air particulate matter by ion chromatography / Mohd Zahari Abdullah @ Rafie and Rahmalan Ahmad - Abdullah @ Rafie, Mohd Zahari; Ahmad, Rahmalan (Universiti Teknologi MARA Cawangan Pahang, 2000)
In recent years, ion chromatography has been increasingly used for the separation and determination of heavy metals. In this study, the separation of Cu2+ Ni2+, Zn2+ and Pb2+ in airborne particuIate sampIes was achieved by the use a complexing eluent containing 20 mM oxalic acid and 20 mM citric acid adjusted to pH 3.6 with lithium hydroxide. Upon elution, the separated metal ions were reacted with PAR (4-(2-pyridylazo) resorcinol to form coloured complexes in a postcolumn reactor and detected by using a UV-Vis detector at 520 nm. Detection limits for a 25-ul sample solution were 2.2, 0.9, 6.6 and 1.8 ug/l for respectively metals. The technique was optimized and validated by analysing the NIST standard reference materials SRM 1648 Urban Particulate Matter and SRM 1633b Coal Fly Ash.